The knowledge of mothers on prevention of diarrhea in infancy - Szewczak, Agnieszka; Bąk, Jadwiga; Węgorowski, Paweł; Zarzycka, Danuta (Journal of Education, Health and Sport, 2018)
Introduction. The incidence of rotavirus diarrhea etiology is one of the most common causes of gastrointestinal diseases of children around the world. It is estimated that rotavirus infections each year (in the world) are the cause of 138 million episodes of diarrhea among children under five years of age. Rotavirus infections are still prominent and growing epidemiological problem in our country. Thus, the need for effective and multidimensional prevention is incredibly important.Aim. Understanding the level of mothers’ knowledge about the prevention of diarrhea among children during infancy.Material and methods. In the study, there was used a method of diagnostic survey questionnaire copyright, composed of 31 closed questions. The research group was 116 mothers of children under 2 years staying in USzD due to the illness of their child.Results. 93.10% of the surveyed recognized that the lack of environmental cleanness, and the lack of hygiene during preparation and serving of meals are the direct cause of the formation of diarrhea and know that the infant is most susceptible to diarrhea (62.93%). mother aged between 25-30 years have significantly higher level of knowledge about the probiotics (80.56%) than polled aged 25 years (47.83%) and more than 30 years (71.93%) (p = 0, 04). The respondents with higher education more often have a higher level of knowledge of probiotics (78.12%), compared to the respondents with high school diploma only (69.45%) or primary and professional education(37.50%) (p = 0.01) • Statistical analysis showed that affluent respondents more commonly have a high level knowledge of the vaccination against rotavirus infections (50.00%) (p = 0.0008).Conclusions. Mothers’ knowledge of prevention of diarrhea children in infancy is insufficient, moreover, most mothers are not aware of significant impact on the prevention of diarrhea proper compliance with the rules of personal hygiene to their children.The vast majority of mothers have a high level of knowledge of the impact of administration of probiotics in the diet of infants on prevention of diarrhea, however, almost 50.0% of the mothers have a low level of knowledge about the vaccination against rotavirus.